2017
DOI: 10.1149/2.0311706jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 475°C Embrittlement of Duplex Stainless Steel Microstructure via Scanning Kelvin Probe Force Microscopy and Magnetic Force Microscopy

Abstract: Scanning Kelvin probe force microscopy (SKPFM) measured local Volta potentials in microstructure of 22Cr-5Ni duplex stainless steel have been correlated to microstructure development with aging treatments at 475 • C. Magnetic force microscopy (MFM) was employed to differentiate crystallographic phases to provide complementary information. The absolute Volta potentials of both ferrite and austenite increased after 5 hours of aging, indicating electrochemical ennoblement of the entire microstructure. Longer agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 61 publications
4
48
0
Order By: Relevance
“…Nilsson et al [34] heat-treated 22Cr-3Mo-8Ni weld metal and reported that spinodal decomposition of ferrite caused embrittlement accompanied by a hardness increase at the same temperature. Örnek et al [35] used Volta potential testing and verified that ferrite decomposition reduced the Volta potential difference between ferrite and austenite in type 2205 DSS resulting in a similar etching behavior of the two phases. Therefore, the etching response and hardness increase together are strong indications of ferrite decomposition, so-called 475°C embrittlement, occurring in the weld metal in the 10 min sample.…”
Section: Hardnessmentioning
confidence: 99%
“…Nilsson et al [34] heat-treated 22Cr-3Mo-8Ni weld metal and reported that spinodal decomposition of ferrite caused embrittlement accompanied by a hardness increase at the same temperature. Örnek et al [35] used Volta potential testing and verified that ferrite decomposition reduced the Volta potential difference between ferrite and austenite in type 2205 DSS resulting in a similar etching behavior of the two phases. Therefore, the etching response and hardness increase together are strong indications of ferrite decomposition, so-called 475°C embrittlement, occurring in the weld metal in the 10 min sample.…”
Section: Hardnessmentioning
confidence: 99%
“…The magnitude of the Volta potential difference between dissimilar microstructural constituents is a quantitative measure for microgalvanic corrosion [35,36,47,49,50,52,[57][58][59][60][61][62]. Therefore, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a galvanic couple, the phase with higher electrochemical nobility has typically higher Volta potentials and usually acts as the cathode, whereas that with lower Volta potentials acts as the anode [47,48]. For a detailed interpretation of the polarity the reader is referred to previous works [47,49,52].…”
Section: Volta Potential Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…38 Selective dissolution of the ferrite phase may be more likely in DSS due to the lower corrosion potential of the ferrite than that of the austenite in chloride-containing environments. 36,[39][40][41][42][43] However, selective attack of the austenite may also be possible if the oxidising power of the electrolyte is sufficiently high, where the ferrite remains passive. [39][40][41][42] The extent of surface corrosion and the dissolved volume slightly increased with exposure time, as shown in Fig.…”
Section: Corrosion Tests-grade 2205 Dssmentioning
confidence: 99%